Seascape connectivity exerts differing effects for fish assemblages in distinct habitats of the surf zones of ocean beaches. (3rd March 2020) - Mosman, Jesse D; Henderson, Christopher J; Olds, Andrew D; Gilby, Ben L; Schlacher, Thomas A
Abstract: Animals move throughout coastal seascapes to disperse, feed, and spawn, including the surf zones of ocean beaches. Yet, the influences of seascape context on surf-zone fish are largely unquantified. We sampled surf-zone fish assemblages with baited remote underwater video deployments at 25 beaches across 50 km of coastline in eastern Australia to determine if variation in the spatial configuration of broader coastal seascapes shapes fish assemblages in different surf-zone habitats. We show that surf zones are not homogenous fish habitats, with offshore bars and nearshore troughs having distinct fish assemblages, shaped by different environmental variables. Fish assemblages of offshore bars were characterized by greater species richness and a higher abundance of indicator species (as identified by Dufrene–Legendre indicator species analysis) when close to rocky reefs and estuaries. In contrast, fish assemblages of nearshore troughs were characterized by greater species richness and a higher abundance of indicator species when far from estuaries, and off wider beaches. Our results highlight the importance of seascape connectivity in structuring surf-zone fish assemblages. Consequently, management approaches need to more thoroughly quantify the effects of seascape connectivity over smaller spatial scales and consider surf zones as key components of broader coastal habitat mosaics.